Дослідження реологічних властивостей харчових систем на основі уронатних полісахаридів - Кондратюк, Наталія Вячеславівна; Пивоваров, Євген Павлович; Грецька, Оксана Володимирівна (НТУ "ХПІ", 2017)
Досліджено реологічні властивості гелів харчових плівкоутворюючих на основі композиції «альгіанат натрію-пектин» за загальним вмістом сухих речовин 3%. Доведено, що зміни в’язкості залежать від кількісних співвідношень полісахаридів уронатного типу. Зі збільшенням пектинової складової спостерігаються два «падіння» динамічної в’язкості системи, що пов’язано з фазовими переходами та масопереносом вологи у системі гелю. У статті обгрунтовано раціональні співвідношення складових у системі, які дозволяють отримати гелі з високими технологічними характеристиками.

At present, ecologically safe, non-toxic, water-soluble polysaccharides, as sodium alginate and low-esterified pectin and complex systems based on them are widely used as stabilizers for a variety of disperse systems, in particular hydrogels and food coatings. Most often, the stabilizing effect is due to a marked change in the viscosity of the dispersion medium. Only some modified polysaccharides have a pronounced activity to bind metal ions and the formation of dense hydrogels capable of solidification, depending on the concentration of polysaccharides and structurants. This ability is exhibited by the polysaccharides of the manmade structure. Currently, such systems are actively used in the production of various medicinal wound dressings, cosmetic products and very rarely as food coatings. To achieve the desired properties as food coverings, we have studied the rheological characteristics of solutions of uronate polysaccharides of different composition with a total amount of dry matter - 3%. In this paper, the influence of the composition of hydrogels on the dynamic viscosity of solutions was investigated. The concentrations of sodium alginate (A) and pectin (P) were represented by the following ratios: 3 : 0; 2.7 : 0.3; 2.1 : 0.9; 1.5 : 1.5; 0.9 : 2.1; 0.3 : 2.7, respectively. Concentrations are expressed in wt.%. The rheological properties of the system were studied using a rotational viscosimeter VPN-0.2. The work used a controlled shear stress, the tests were conducted at 20 ° C. The viscosity of the solutions depended on the ratio of the concentrations of polysaccharides. The "anomalous" decrease in viscosity was twice fixed from 0.306 to 0.175 Pa · sec and from 0.213 to 0.188 Pa · sec, which allows us to judge the formation of layers in solutions that have the properties of a non-newtonian liquid.
Research of rheological properties of the food systems based on uronate polysacharides
Keywords: альгінат натрію; пектин низькоетерифікований; пектин амідований; гель; в'язкість динамічна; реологія; alginate sodium; low-esterified pectin; amidated pectin; gel; dynamic viscosity; rheology